Hydraulic trade-off and coordination strategies mediated by leaf functional traits of desert shrubs - Huo, Jianqiang; Shi, Yafei; Chen, Jiajia; Zhang, Hongxia; Feng, Li; Zhao, Yang; Zhang, Zhishan (Frontiers in Plant Science, 2022)
Desert shrubs play important roles in desertification control and vegetation restoration, which are particularly affected by droughts caused by climate change. However, the hydraulic strategies associated with hydraulic functional traits of desert shrubs remain unclear. Here, eight desert shrub species with different life forms and morphologies were selected for a common garden experiment at the southeast edge of the Tengger Desert in northern China to study the hydraulic strategies mediated by leaf hydraulic functional traits. Diurnal leaf water potential change, leaf hydraulic efficiency and safety, and hydraulic safety margin, hydraulic capacitance and water potential and relative water content at the turgor loss point were observed to significantly differ among species, suggesting that leaf hydraulic functional traits were more strongly associated with species but irrespective of environment. Additionally, shrubs with greater leaf hydraulic efficiency had lower midday leaf water potential and leaf hydraulic safety, suggesting that leaf hydraulic efficiency had a strong trade-off with hydraulic safety and minimum leaf water potential, while there was also a coordination between leaf hydraulic safety and the leaf minimal water potential. Moreover, shrubs with higher leaf hydraulic capacitance had greater hydraulic safety margins, indicating coordination between leaf hydraulic capacitance and hydraulic safety margin. Overall, this study indicated that minimal daily leaf water potential, as an easily measured parameter, may be used preliminarily to predict leaf hydraulic conductivity and the resistance to embolism of desert shrubs, providing critical insights into hydraulic trade-off and coordination strategies for native shrubs as priority species in desert vegetation restoration and reconstruction.